1940
DOI: 10.1111/j.1469-185x.1940.tb00947.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactation

Abstract: Summary 1. In most species oestrogens mainly stimulate mammary duct growth. In the guinea‐pig and goat they promote complete alveolar development. The mouse is the only animal in which treatment with progesterone has been found to promote mammary duct growth. In other species simultaneous treatment with oestrogens and progesterone is necessary for complete alveolar development. It is difficult to say whether or not oestrogens per se can promote alveolar development, because the adrenal cortex produces progeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1940
1940
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 177 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Recently it has been claimed that a rapid proliferation (or growth) of cells may be correlated with a high content of ribonucleic acid (Brachet, 1941;Thorell, 1947) and/or of alkaline phosphatase (Danielli, 1946;Moog, 1946), 10 MR B. I. BALINSKY ON THE DEVELOPMENTAL PROCESSES IN both of which substances may be demonstrated by cytochemical methods. The alkaline phosphatase is of special interest in this connection, as it has a specific relation to the differentiation of hairs (my attention has been drawn to this fact by Miss M. H. Hardy, 1949), and is also present in fully differentiated milk-gland tissue (Folley, 1940). The content of the ribonucleic acid in different stages of growth and differentiation of embryonic structures is of special interest as it has been suggested that it may be playing a very prominent role in the determination of tissues and cells (Brachet, 1944;Darlington, 1944;Wright, 1945;Spiegelman, 1948).…”
Section: The Changes In Cytochemical Properties Correlated With the Pmentioning
confidence: 99%
“…Recently it has been claimed that a rapid proliferation (or growth) of cells may be correlated with a high content of ribonucleic acid (Brachet, 1941;Thorell, 1947) and/or of alkaline phosphatase (Danielli, 1946;Moog, 1946), 10 MR B. I. BALINSKY ON THE DEVELOPMENTAL PROCESSES IN both of which substances may be demonstrated by cytochemical methods. The alkaline phosphatase is of special interest in this connection, as it has a specific relation to the differentiation of hairs (my attention has been drawn to this fact by Miss M. H. Hardy, 1949), and is also present in fully differentiated milk-gland tissue (Folley, 1940). The content of the ribonucleic acid in different stages of growth and differentiation of embryonic structures is of special interest as it has been suggested that it may be playing a very prominent role in the determination of tissues and cells (Brachet, 1944;Darlington, 1944;Wright, 1945;Spiegelman, 1948).…”
Section: The Changes In Cytochemical Properties Correlated With the Pmentioning
confidence: 99%
“…method which, however, can give little insight into the synthetic mechanisms involved. Arterio-venous studies have disproved the earlier idea of the utilization of blood phospholipin fatty acids for milk fat synthesis and have provided evidence that fatty acids of neutral fat, probably belonging to the glyceride fraction, are absorbed from the blood by the lactating udder, and are there transformed into glycerides of milk fat (see reviews by Folley, 1940Folley, , 1949. Because they obtained a high respiratory quotient (R.Q.)…”
mentioning
confidence: 99%
“…The organism is, however, less specific towards the pyrimidine group, the following substitutes for the aneurin base being active in approximately the same concentration, 'uuz'x., 4-amino-5-thioformamidomethyl-2 -methylpyrimidine and 4 -amino-5-aminomethyl-2 -methylpyrimidine ; inactive, however, were 4-hydroxy-5-hydroxymethyl-2 -methylpyrimidine, 4-hydroxy-5-aminomethyl-2-methylpyrimidine, and 4-amino-2-hydroxypyrimidine (cytosine). 22 The anaerobic metabolism of Staph. aureus is different from its aerobic metabolism; in the former case it derives its energy mainly from amino-acids ; anaerobically from glucose and pyruvic acid.…”
Section: J H Muellermentioning
confidence: 99%